Jurnalisme Buddhis di Negara Mayoritas Islam: Kajian Etnografi di DAAI TV - Wirawan, Wirawan (Magister of Communication Science, Sahid University Jakarta., 2023)
Journalism is ideally a secular practice. However, there are a number of press institutions associated with religious organizations in Indonesia, such as DAAI TV, which was established by the Yayasan Buddha Tzu Chi Indonesia. This research explores the role of Buddhist religious values in shaping journalistic practices at DAAI TV. The data were gathered using the ethnographic method through participant observation, in-depth interviews, and document analyses from August 2019 to April 2020. Implementing the framework of Buddhist-oriented journalism concepts introduced by Gunaratne (2009) and Pearson and Senarath (2015), this study indicates that DAAI TV has brought the notion of Buddhist journalism to life, despite the fact that not all of its journalists are Buddhists. In terms of ethics, DAAI TV actualized Buddhist journalism by incorporating sammÄ-vÄcÄ (right speech), sammÄ-kammanta (right action), and sammÄ-Äjiva (right livelihood) into their journalistic practice.